2007
DOI: 10.1563/1548-1336(2007)33[59:cdiwha]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Cylindrical Dental Implants With Hydroxyapatite- and Titanium Plasma Spray–coated Surfaces: 5-year Results

Abstract: Clinical follow-up was conducted on 127 cylindrical implants placed in 21 patients after 5 years of function: 75 implants were coated with titanium plasma spray (TPS) and 52 implants were coated with hydroxyapatite (HA). The aim of the study was to assess possible differences in clinical function and success rates for each implant type. Clinical and radiographic evaluations were conducted, and the periodontal indices of gingival bleeding, plaque, and calculus were measured. Cumulative data were analyzed for di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 22 publications
0
10
0
1
Order By: Relevance
“…Screening the abstracts led to 20 full-text articles, which are detailed in Tables 1 and 2. From these articles, 15 reports (Callan et al 2000;Groisman et al 2001;Mau et al 2002;Jeffcoat et al 2003;Davis et al 2004;Griffin & Cheung 2004;Rosenberg et al 2004;Taylor et al 2004;Schwartz-Arad et al 2005;Simunek et al 2005;Degidi et al 2006;Ko et al 2006;Capilla et al 2007;Matsui et al 2007;Lee et al 2010) were excluded for reasons mentioned in Tables 1 and 2. Finally, five of these original research reports could be selected for evaluation (Tinsley et al 2001;McGlumphy et al 2003;Artzi et al 2006;Binahmed et al 2007;Thierer et al 2008) and are summarized in Tables 1 and 2.…”
Section: Study Selectionmentioning
confidence: 99%
“…Screening the abstracts led to 20 full-text articles, which are detailed in Tables 1 and 2. From these articles, 15 reports (Callan et al 2000;Groisman et al 2001;Mau et al 2002;Jeffcoat et al 2003;Davis et al 2004;Griffin & Cheung 2004;Rosenberg et al 2004;Taylor et al 2004;Schwartz-Arad et al 2005;Simunek et al 2005;Degidi et al 2006;Ko et al 2006;Capilla et al 2007;Matsui et al 2007;Lee et al 2010) were excluded for reasons mentioned in Tables 1 and 2. Finally, five of these original research reports could be selected for evaluation (Tinsley et al 2001;McGlumphy et al 2003;Artzi et al 2006;Binahmed et al 2007;Thierer et al 2008) and are summarized in Tables 1 and 2.…”
Section: Study Selectionmentioning
confidence: 99%
“…An excellent survival rates were reported for titanium plasma sprayed (TPS-coated) implants exceeding 95% after 5 years to 11 years of clinical functioning, long-term predictability for TPS -coated implants can be comparable with or superior to other implant surfaces. 6 However, another study was performed to compare the prosthetic and implant failures of immediately loaded single implants with a machined or a roughened surface (sand-blasted with zirconia powder and acid etched), both groups showed good and similar results with no statistically significant differences. 11 Another study was done to evaluate the biologic response of titanium Implants with machined surface versus laser-Treated Surfaces , it revealed that the analysis of bone repair on the roughened laser-treated surfaces demonstrated direct contact between the bone (mineralized interfacial matrix) and the implant, suggesting mechanical penetration of the irregularities of the superficial roughness promoted by this surface morphology, as well as oxide layer modification.…”
Section: Discussionmentioning
confidence: 99%
“…Coating resorption of TPS implants is also reported, it may be related to the quality of the coatings studied which had low-density, low microhardness and showed microcracks with poor bonding strength between coating and implant. 6 However, on the contrary, it was reported that after 3 years follow up period, implants with a very rough surface have a 20% increased risk of being affected by peri-implantitis. The difficulties in the treatment of peri-implantitis and the questionable long-term prognosis of implant cases affected by peri-implantitis, caused some doubts on the success of rough surface implants, in particular of those treated with titanium plasma-sprayed techniques, making the use of implants with machined surfaces more durable and interesting once again.…”
Section: Marginal Bone Loss Around Machined Versus Plasma Sprayed Impmentioning
confidence: 97%
See 1 more Smart Citation
“…DISCUSSÃOpromover e diminuir o tempo de osseointegração. A criação de micro rugosidades, assim como a incorporação de substâncias bioativas, como o fosfato de cálcio (Hidroxiapatita), íons cálcio e magnésio ou proteínas ósseas morfogênicas, pode acelerar e aumentar a formação óssea, envolta dos implantes(BIESBROCK, EDGERTON, 1995; JEFFCOAT et al, 2003;SUL, JOHANSSON, ALBREKTSSON, 2006;CAPILLA et al, 2007).Implantes dentários feitos com Biocerâmica (zircônia) são utilizados com a finalidade de evitar os problemas inerentes aos implantes tradicionais (metálicos, poliméricos), como a liberação de íons e/ou fratura do osso (gradiente dos módulos de elasticidade), ou ainda com a sensibilidade do organismo com a maioria dos materiais estranhos, podendo resultar na formação de uma camada não aderente de substância fibrosa ao redor do implante(HENCH, 1986). Por isso o que se espera com estudos futuros envolvendo a cerâmica de hidroxiapatita é melhorar suas propriedades mecânicas, associando-as a outros materiais, estando em harmonia com suas excelentes propriedades biológicas.7 CONCLUSÕES…”
unclassified